The Biological Properties of the Strain Francisella tularensis 15 NIIEG with Decreased Gene Expression sodB, Encoding Fe-Dependent Superoxide Dismutase - M. A. Sotnikova; T. B. Kravchenko; I. V. Bakhteeva; R. I. Mironova; T. I. Kombarova; A. N. Mokrievich; V. M. Pavlov (Эпидемиология и вакцинопрофилактика, 2016)
Relevance. Superoxide anion has bactericidal properties and is also an important inducer of proinflammatory cytokines in macrophages. We have created F. tularensis 15/sodBII strain with transiently decreased FeSOD synthesis level and more sensitive to oxidative stress. So we suggest that the modified vaccine strain have lower reactogenicity. Goal. Studying of effect of sodB gene expression modulation on biological properties of vaccine F. tularensis strain 15 NIIEG. Materials and methods. F. tularensis survival in macrophage-like cell line J774.1A and in spleen and liver of infected mice were analyzed through colony-forming unit enumeration. Strains reactogenicity was assessed by the dynamics of change in weight of infected mice. Efficacy of immune response generated by mutant strain of F. tularensis 15/sodBII was estimated with virulent F. tularensis strain Schu S4 infection in the BALB/c mice model. Results. Degree of protection was significantly more pronounced in the mice vaccinated with the strain F. tularensis with decreased sodB gene expression in comparison with parental F. tularensis strain NIIEG 15. Conclusions. The modified strain of F. tularensis 15/sodBII may be consider as a promising variant for development of a new tularemia vaccine with reduced reactogenicity.